Rowley Jefferson's awesome friendly spooky stories - Kinney, Jeff (New York : Amulet Books, 2021)
"Grab a flashlight, crawl under the covers, and dive into the twisted, unexpectedly hilarious world of Rowley Jefferson's imagination. You'll meet zombies, vampires, ghosts, and much more in these comically terrifying tales. Rowley's spooky stories might leave you laughing, but beware-- you could end up sleeping with the lights on"--Provided by publisher.
The Changing -- The Prankster -- Ghost Friend -- The Biter -- The Human Head -- The Scanner -- The Cellar -- The Nap -- The Stain -- a mummy -- The Science Project -- The Medicine Cabinet -- The Invasion -- The Demon.
Ages 8 to 13
Keywords: Friendship -- Juvenile fiction; Ghost stories; Action and adventure fiction; Paranormal fiction; Humorous fiction; Short stories